BREAKING THE BOUNDARIES OF PATRIARCHY: ELABORATION OF THE PILLARS OF MODERN ISLAMIC THOUGHT ON WOMEN'S LEADERSHIP - Munir, Abdullah; AM, Hurin'in; Bahauddin AM, Ahmad (Journal of Islamic Studies and Humanities, 2024)
Women's leadership in the context of modern Islamic thought is a topic that is gaining increasing attention. In many societies, the traditional paradigm of women's role in leadership is still dominant. Therefore, there is an urgent need to reconstruct and elaborate the pillars of Islamic thought in order to better support women's participation in leadership. This study aims to investigate women's leadership roles and detail steps to reconstruct and elaborate the pillars of modern Islamic thought to facilitate women's participation in leadership. A special goal is to identify barriers faced by women in achieving leadership positions and explore strategies that can be used to overcome these barriers. A qualitative approach was used in this study. An in-depth literature analysis was conducted to evaluate traditional Islamic thought and find a basis for the reconstruction of that thought. In addition, in-depth interviews with Islamic thought figures and women leaders were conducted to gain practical perspectives and experience in facing leadership challenges. The results suggest that through the reconstruction of modern Islamic thought, it is possible to create an environment that supports and encourages women to take leadership roles. Strategies involving women's education, advocacy, and capacity building have proven effective in overcoming these barriers. Therefore, this research contributes to our understanding of how the reconstruction of Islamic thought can support women's active participation in leadership.